Differences in Behavioral Health Treatment among Rural American Clinics Utilizing In-Person and Telehealth Treatment Modalities - Law, Kari-Beth; McCord, Carly; Ward, Marcia M.; Ullrich, Fred; Marcin, James P.; Carter, Knute D.; Nelson, Eve-Lynn; Merchant, Kimberly A. S. (Journal of technology in behavioral science, 2025)
The purpose of this descriptive analysis is to compare patient and encounter characteristics in rural patients who received telehealth versus in-person behavioral health treatment. This study, including over 11,000 rural patients and nearly 35,000 patient encounters, used a non-randomized prospective research design involving two active usual-care treatment groups—a behavioral telehealth treatment group and an in-person behavioral health treatment group. Two-tailed chi-square tests compared treatment groups on patient characteristics and encounter-level variables. Statistically significant differences were found between the telehealth and in-person treatment groups in age, race, ethnicity, primary diagnosis, provider type, service type, insurance status, and treatment billing (all p < 0.001). The telehealth treatment group was more likely to be Hispanic, aged 18 and younger, with ICD-10 diagnoses related to that age group, have government-financed insurance, receive office and outpatient visits for evaluation and management psychiatric services, and be seen by a wide range of providers. The in-person treatment group was more likely to be aged 19–34; have private insurance; have a primary ICD-10 diagnosis of anxiety, dissociative, stress-related, somatoform, and other nonpsychotic mental disorders; receive treatment by clinical social workers; and have 60-min individual therapy. This analysis of real-life data from 95 rural clinic sites in 13 states largely validates national survey data regarding the utilization of telehealth in specific underserved populations but expands these findings to show continued disparities in provider, service, and payer type, which is particularly important for rural communities and pre-existing healthcare equity concerns.